Aqueous Stable Gold Nanostar/ZIF‐8 Nanocomposites for Light‐Triggered Release of Active Cargo Inside Living Cells. Issue 21 (12th April 2019) - Carrillo‐Carrión, Carolina; Martínez, Raquel; Navarro Poupard, María F.; Pelaz, Beatriz; Polo, Ester; Arenas‐Vivo, Ana; Olgiati, Alessandro; Taboada, Pablo; Soliman, Mahmoud G.; Catalán, Úrsula; Fernández‐Castillejo, Sara; Solà, Rosa; et al.
Abstract: A plasmonic core–shell gold nanostar/zeolitic‐imidazolate‐framework‐8 (ZIF‐8) nanocomposite was developed for the thermoplasmonic‐driven release of encapsulated active molecules inside living cells. The nanocomposites were loaded, as a proof of concept, with bisbenzimide molecules as functional cargo and wrapped with an amphiphilic polymer that prevents ZIF‐8 degradation and bisbenzimide leaking in aqueous media or inside living cells. The demonstrated molecule‐release mechanism relies on the use of near‐IR light coupled to the plasmonic absorption of the core gold nanostars, which creates local temperature gradients and thus, bisbenzimide thermodiffusion. Confocal microscopy and surface‐enhanced Raman spectroscopy (SERS) were used to demonstrate bisbenzimide loading/leaking and near‐IR‐triggered cargo release inside cells, thereby leading to DNA staining. Abstract : Triggered release : A thermoresponsive carrier comprising gold nanostars coated with ZIF‐8 stabilized with an amphiphilic polymer was developed for the light‐triggered release of encapsulated cargo inside cells. This nanocomposite, which is stable in aqueous solution (even when stored in cells), combines thermoplasmonic and high drug‐loading capabilities.